ESTUDO DE FORMULAÇÕES ENZIMÁTICAS ENVOLVENDO β-TRIPSINA BOVINA COM MAIOR ATIVIDADE E ESTABILIDADE EM FUNÇÃO DA CONCENTRAÇÃO DE ÍONS PARA ATUAÇÃO EM SISTEMAS DE DETERGENTES E SAPONÁCEOS COMERCIAIS - Vasconcelos, Antonio Victor Baioco (2020)
Household cleaning is a daily worldwide activity, which means that billions of people use detergents to clean their clothes, dishes, and so forth. The enzymes are increasingly added to achieve "catalytic cleaning", thereby creating smaller fragments of th